新加坡华族社团的发展途径 ：南洋潘氏总会与琼崖潘氏社的比较研究 = Development of Singapore Chinese Clan Associations : a comparative study between Nanyang Phua Clan Association and Heng Jai Phua Clan Association - 潘在轩 Phua, Tai Shuen (Nanyang Technological University, 2020)
由19世纪至二战，大量华人逃离中国内忧外患，移民来到新加坡，当时的英国殖民地政府施予社会的帮助有限，导致华人移民为了自助而开创会馆，以宗亲（血缘），同乡（地缘），行业（业缘）为三大类型，发展脉络分为创立与发展（1819-1959），沉默 （1960-1985），和转型（1985-至今）三个时期。1960至1980年代，新加坡开启建国的步伐，政府建构国家认同来团结社群。1987年，国家认同在英文正式成为国家教学媒介后而加速递进，政府也逐渐取代以往华人社团所实行的社会功能。由1960年代起，新加坡华人会馆都面对会员减少和老化的问题。在新加坡华人宗乡会馆当中，存有两间在1950至60年代昌盛的潘氏会馆 – 新加坡南洋潘氏总会、新加坡琼崖潘氏社。血缘性组织的南洋潘氏总会，容纳所有籍贯的潘氏族群为会员，以潘氏宗亲为主要身份认同，设潘府大人为节日祭拜对象。相比之下，血缘和地缘双性组织的琼崖潘氏社，会员只存有来自海南岛的潘氏宗亲。以潘氏宗亲和海南人为身份认同，设季孙公和海南潘氏始祖为祭拜对象。两者以培育下一代和国际化发展为生存策略，如今双方依然维持着会馆的经营。 From the 19th century till World War 2, a significant number of Chinese migrated to Singapore to escape the dire issues in China. The British Colonial rule provided limited help and resources for Chinese immigrants and thus they had to establish clan associations on their own, which can be divided into three main types: kinship, locality, industry. The development of the clan associations can be periodized into Establishment and Development (1819-1959), Decline (1960-1985), and Transformation (1985 till now). Singapore embarked on the project of nation building in the 1960-80s, uniting the multicultural society under a national identity. National identity was further strengthened in 1987 when English became the official communication language in Singapore education. Concurrently, the societal role of the clan associations was gradually taken over by various government organizations. Since the early 1960s, Singapore Chinese clan associations have been in decline due to shrinking membership and the ageing members. Amongst all the kinship clan associations, there are two Phua clan associations namely Nanyang Phua Clan Association and Heng Jai Phua Clan Association. Nanyang Phua Clan Association is a type of kinship clan association, consisting of Chinese descendants with the surname of Phua across different dialects. The members identify themselves as Phua descendants and pay respect to Lord Pan. On the other hand, Heng Jai Phua Clan Association is both locality and kinship type of clan association, only taking in Hainanese with the surname of Phua. The members regard themselves as Phua descendants from Hainan Island, and pray to Ji Sun Gong and their ancestors from Hainan Island. Till this date, both clan associations have survived the decline of clan associations via the shift in focus towards globalization and providing aid for the younger generation’s education.